Ruislag Procedure of Waqf Land Affected by National Strategic Projects in the Perspective of State Administrative Law - Tatang Astarudin (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Waqf land plays an important legal and social role in Indonesia, particularly to support religious activities and public welfare. Under Law No. 41 of 2004 on Waqf, waqf land may not be transferred except through exchange or ruislag procedures under certain conditions. In the context of National Strategic Projects (PSN), waqf land is often affected, making it important to ensure that ruislag procedures remain legally compliant. This research aims to explore the ruislag procedure of waqf land in PSN and evaluate its application to identify improvements in state administrative law. This research utilises the normative juridical method. The research found that the ruislag process of waqf land affected by National Strategic Projects (PSN) requires strong coordination between the Indonesian Waqf Board, the Ministry of Religious Affairs, and other relevant institutions. It is important to ensure that the replacement land has equal or better value, in accordance with sharia principles and applicable laws. Active participation of beneficiary communities is essential to maintain transparency and public trust.